Specjalna zdolność prawna osób prawnych: [Special legal capacity of legal persons] (Studia Prawnicze / The Legal Studies, 2023)
Autor artykułu przedstawia swoje rozważania nad art. 36 k.c., który normuje sytuację prawną osób prawnych. Z przepisu wynika, że zdolność prawna osób prawnych jest zdolnością specjalną. Zdolność ta, została poddana licznym ograniczeniom. W niniejszej pracy porównano rozwiązania prawne innych państw socjalistycznych, gdzie wskazano różnice w konstrukcji specjalnej zdolności prawnej. Autor przedstawia swoją krytyczną analizę instytucji zdolności specjalnej osób prawnych przytaczając różnorodne przykłady spraw spornych wynikających z obecnych uregulowań a także bogatą literaturę przedmiotu. The author of this article presents his reflections on Article 36 of the Civil Code, which regulates the legal status of legal persons. It follows from the provision that the legal capacity of legal persons is a special capacity. This capacity, has been subject to a number of restrictions. This study compares the legal solutions of other socialist countries, where differences in the construction of special legal capacity are indicated. The author presents his critical analysis of the institution of the special capacity of legal persons citing various examples of litigation arising from the current regulations as well as a wealth of literature on the subject.